Digit symbol substitution test score and hyperhomocysteinemia in older adults. Issue 35 (August 2016) - Hsu, Wen-Chuin; Chu, Yi-Chuan; Fung, Hon-Chung; Wai, Yau-Yau; Wang, Jiun-Jie; Lee, Jiann-Der; Chen, Yi-Chun
Abstract : Abstract: Mounting evidence shows that hyperhomocysteinemia is a risk factor for cognitive decline. This study enrolled subjects with normal serum levels of B12 and folate and performed thorough neuropsychological assessments to illuminate the independent role of homocysteine on cognitive functions. Participants between ages 50 and 85 were enrolled with Modified Hachinski ischemic score of <4, adequate visual and auditory acuity to allow neuropsychological testing, and good general health. Subjects with cognitive impairment resulting from secondary causes were excluded. Each of the participants completed evaluations of general intellectual function, including the Mini-Mental State Examination, Cognitive Abilities Screening Instrument, Clinical Dementia Rating, and a battery of neuropsychological assessments. This study enrolled 225 subjects (90 subjects younger than 65 years and 135 subjects aged 65 years or older). The sex proportion was similar between the 2 age groups. Years of education were significantly fewer in the elderly (7.49 ± 5.40 years) than in the young (9.76 ± 4.39 years, P = 0.001). There was no significant difference in body mass index or levels of vitamin B12 and folate between the 2 age groups. Homocysteine levels were significantly higher in the elderly group compared to the younger group (10.8 ± 2.7 vs. 9.5 ± 2.5 μmol/L, respectively, P = 0.0006). After adjusting for age, sex, and education, only the Digit Symbol Substitution (DSS) score was significantly lower in subjects with hyperhomocysteinemia (homocysteine >12 μmol/L) than those with homocysteine ⩽12 μmol/L in the elderly group (DSS score: 7.1 ± 2.7 and 9.0 ± 3.0, respectively, beta = −1.6, 95% confidence interval [CI] = −2.8∼−0.5, P = 0.001) and borderline significance was noted in the combined age group (beta = −1.1, 95% CI = −2.1∼−0.1, P = 0.04). We did not find an association between hyperhomocysteinemia and other neuropsychological assessments. This is the first study to demonstrate a significant association between hyperhomocysteinemia (>12 μmol/L) and low DSS score, suggesting that DSS score may be an independent marker of cognitive impairment in response to hyperhomocysteinemia, especially in the elderly. Further replication studies with larger cohorts are needed to confirm our results.